Research on The Integrated Education Adaptability of Visually Impaired Students—A Study on Binzhou Medical University from China - ZhouBo; Kway Eng Hock (International Inclusion Development and Cooperation, 2023)
The education of visually impaired students in China has also gone through a developmental stage from